Somatostatin: a paracrine contribution to hypothyroidism in Hashimoto's thyroiditis. Issue 7 (July 1982) - Dhillon, A P; Rode, J; Leathem, A; Papadaki, L
Abstract : Thyroid tissue from 18 consecutive cases of Hashimoto's thyroiditis treated surgically were stained immunohistochemically for neurone specific enolase (NSE), somatostatin, calcitonin and thyroglobulin. Cells staining for NSE and somatostatin were present in 14 cases. In four cases large numbers of cells including oxyphil cells stained for NSE. Consecutive sections showed an identical staining pattern of these cells for somatostatin. Sections stained for calcitonin showed few or no positively staining cells. There were moderate numbers of NSE and somatostatin-containing cells in five of the cases, occasional cells in five and none in four cases. Electron microscopy confirmed neurosecretory-like granules within positively staining cells. Somatostatin is known to inhibit T3 and T4 production or release from thyroid cells by a direct action. We suggest, in Hashimoto's disease, somatostatin in paracrine cells serves as a local inhibitory neuroendocrine effector and could be causally related to the hypothyroid state.